Immunological clearance of 75Se-labelled Trypanosoma brucei in mice. I. Aspects of the radiolabelling technique. - Holmes, P H (1979)
A reliable and simple technique for the in vivo labelling of Trypanosoma brucei with [75Se]-methionine was developed. Between 97 and 99% of the radioactivity was protein bound in the trypanosomes and spontaneous elution in vitro was less than 10% over 4 h. The fate of the labelled trypanosomes after i.v. injection into normal and immune mice was studied. Whilst the vast majority of parasites remained in the circulation of normal animals they rapidly disappeared from the blood of immune animals. In the latter the liver was found to be the principal site of phagocytosis removing over 50% of the radiolabelled parasites within 15 min of injection.